Analysing IoT cyber risk for estimating IoT cyber insurance - Petar Radanliev; Dave De Roure; Stacy Cannady; Rafael Mantilla Montalvo; Razvan Nicolescu; Michael Huth (Living in the Internet of Things: Cybersecurity of the IoT - 2018. IET Conference Proceedings, 2018)
This paper is focused on mapping the current evolution of Internet of Things (IoT) and its associated cyber risks for the Industry 4.0 (I4.0) sector. We report the results of a qualitative empirical study that correlates academic literature with 14 - I4.0 frameworks and initiatives. We apply the grounded theory approach to synthesise the findings from our literature review, to compare the cyber security frameworks and cyber security quantitative impact assessment models, with the world leading I4.0 technological trends. From the findings, we build a new impact assessment model of IoT cyber risk in Industry 4.0. We therefore advance the efforts of integrating standards and governance into Industry 4.0 and offer a better understanding of economics impact assessment models for I4.0.
Keywords: 330; IoT Cyber Risk; IoT risk analysis; IoT cyber insurance; IoT MicroMort; Cyber Value-at-Risk